Alleged fatal motor vehicle accident uncovering the mystery a case report - Zaki, Hafizatul Solehah; Hasim, Husna Syaza; Mussadik, Umul Khairil Fatimah; Chng, Kay Ly (Academy of Medicine Malaysia, 2025)
Introduction: Forensic pathology plays a great role in medical healthcare, particularly in determining the cause of death in medicolegal cases. Often times cases of alleged motor vehicle accidents (MVAs) are associated with traumatic injuries as the primary cause of death. However, in some circumstances, the cause of death is preceded by a natural event. Therefore, there is a crucial need of performing a thorough medicolegal autopsy in such cases to precisely establish the cause of death. This case report explores a fatal MVA in which the driver succumbed to a natural cause, emphasizing the importance of autopsy in distinguishing between traumatic and natural death. Case report: The case involves a 50-year-old male with underlying Diabetes Mellitus who was involved in a minor motor vehicle collision. Despite the lack of significant injuries, the driver was found unresponsive at the scene and was later pronounced dead at Emergency Department. Forensic examination, including a comprehensive autopsy and laboratory investigation, revealed that the death was due to ruptured coronary artery plaque. Conclusion: This case emphasizes the critical importance role of forensic pathology in accurately identifying the cause of death in MVAs, especially when natural causes are suspected. It highlights the need for detailed post-mortem investigations to distinguish between deaths caused by traumatic injuries and those resulting from other underlying medical conditions. The findings further provide precision into establishment of the cause of death, manner of death and mechanism of death which is the foundation in legal proceedings besides contributing in the broader context of public health and safety.